Etika Pemasaran Syariah Solusi bagi Pemasaran yang Adil dan Transparan - Andika Saputra (Jurnal Multidisiplin Indonesia, 2024)
Sharia marketing is a marketing concept based on Islamic principles, emphasizing justice, transparency, and honesty in every transaction. This study aims to analyze the application of sharia marketing ethics in companies and its impact on consumer loyalty and business performance. The research uses a qualitative approach with case studies on several companies that implement sharia principles in their marketing activities. The findings show that companies applying sharia marketing ethics principles successfully enhance consumer loyalty and build better relationships with society, although challenges remain regarding the uneven understanding of sharia principles. The implication of these findings is the importance of further education and socialization to business actors and consumers regarding the values of sharia marketing. This study also suggests the need for further research with a broader and deeper scope to understand the long-term effects of implementing sharia marketing.